FEATURES OF THE MAGNETOREFRACTIVE EFFECT IN NANOSTRUCTURES - A. N. Yurasov (Российский технологический журнал)
We have theoretical investigated the magnetorefractive effect (MRE) in nanostructures. We discuss possibility of magnifications for this effect. MRE can be considered as variations of the coefficients of reflection, transmission and absorption of electromagnetic waves of samples with magnetoresistance (MR) under applied magnetic field. We have deduced formulas for change of the optical constants in magnetic field that does possibility for corrected description spectra of the magnetorefractive effect especially in the near IR region. The results of calculations have been analyzed in comparison with experimental date in the IR range. It was shown that the magnitude and frequency dependencies of MRE are sensitive to the optical properties of the structures, model parameters, their thickness and MR values. It was shown that changes of the optical constants are strictly connected with the magnetoconductivity (magnetoresistance) of the nanostructures under applied magnetic field. So as MRE can be used as contactless method for MC measurements effectively.